Peluang Dan Tantangan Bahasa Indonesia Menjadi Bahasa Dunia : Perspektif Generasi Muda Dalam Era Globalisasi - Ainur Oktania; Jonatan Marbun; Kezia Aritonang; Theresia Sihombing; Yohana Feby; Fitriani Lubis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research tries to analyze the opportunities and challenges of Indonesian as a world language based on the perspective of the younger generation in the era of globalization. The aim is to provide deep insight into how Indonesian can maintain its relevance in the era of globalization. This study used a qualitative approach with data collection techniques in the form of filling out a questionnaire consisting of 6 questions. The results of the research from 56 informants show that the young generation of Indonesia has a crucial role in maintaining and advancing Indonesian as a world language. Technology and social media are considered as effective tools in popularizing this language at the global level.